Lipase activity in biphasic media: Why interfacial area is a significant parameter? - Sunan Saktaweewong (2018)
This work focused on lipase-catalyzed triglyceride hydrolysis in biphasic media. The effect of specific interfacial area of oil-in-water emulsions on the hydrolysis activity of lipase was particularly investigated following a rigorous methodology and using two different oils, tributyrin and olive oil. The specific interfacial area was varied over several orders of magnitude by changing either the amount of emulsified oil or the average diameter of oil droplets. This work particularly focused on the effect of changing droplet size (at given amount of oil) on lipase activity. When the specific interfacial area was varied over several orders of magnitude, the specific activity of the enzyme exhibited a non-monotonic variation with a pronounced maximum. At low specific interfacial area, initial velocity increased with specific interfacial area. Inhibition of enzyme activity at a high interfacial concentration of triglyceride was observed. Experimental results were interpreted on the basis of a theoretical mechanism assuming Michaelis-Menten mechanism for enzyme catalysis, Langmuir-type adsorption isotherm for enzyme and limitation of enzyme-substrate formation by enzyme adsorption process. © 2011 Elsevier B.V.